#patientstoo – Professional sexual misconduct by healthcare professionals towards patients: a representative study. (21st June 2021) - Clemens, V.; Brähler, E.; Fegert, J. M.
Abstract: Aims: Sexual border violations are a severe problem in the healthcare system. Studies using non-probability samples indicate a high prevalence of professional sexual misconduct (PSM) towards patients. However, valid prevalence rates are lacking. Methods: We did a cross-sectional, observational study in Germany from February to April 2020. By different sampling steps, a probability sample of the German population above the age of 14 was generated. The final sample consisted 2503 persons (50.2% female, mean age: 49.5 years). Participants were asked about sexual contacts with and sexual harassment by healthcare professionals. Using descriptive statistics, prevalence rates of PSM were estimated. Results: PSM was reported by 56 (4.5%) female and 17 (1.4%) male participants. In detail, 28 (2.2%) female and 10 (0.8%) male participants reported sexual contacts with healthcare professionals. One third of these sexual contacts took place before the age of 18 and one third against the will of the patients. 40 (3.2%) female and 8 (0.6%) male participants reported unnecessary physical examinations, 31 (2.5%) female and 7 (0.6%) male participants reported sexual harassment. The majority of perpetrators were male. Conclusions: Our data provide an important first insight into the prevalence of PSM by healthcare professionals towards patients in a representative sample. Results suggest a high prevalence of PSM in the general population of Germany. Preventive measures to increase awareness of PSM and concepts for protection of patients are needed.